An Image of a Person with an Autism Spectrum Disorder in Popular Literature (on the Example of the Hero of Jodi Picoult's Novel “House Rules”) - Senderska, Joanna (Respectus Philologicus, 2020)
In this article, the case of eighteen-year-old Jacob Hunt, the main character of Jodi Picoult’s book entitled House Rules (W naszym domu in Polish translation) is discussed. Jacob is an example of a literary character with features similar to those of people with autism spectrum disorders (ASD). He suffers from Asperger syndrome, which belongs to ASD (autism spectrum disorder). That is why he finds it difficult to develop communication skills, which translates into disturbed communication. The disturbances involve difficulties in acquiring and applying social rules as well as having specific narrow interests. The author of this article points out the linguistic, as well as non-linguistic behaviour of the protagonist, which are specific for autism spectrum disorder. She also draws attention to the role that popular literature plays in creating the image of people with ASD and in popularizing information about this disorder.
Keywords: autism spectrum disorder; Asperger syndrome; verbal communication